Income inequality and happiness: which inequalities matter in China? - Knight, J; Gunatilaka, R (Centre for the Study of African Economies, 2021)
The effect of inequality on happiness should intrigue social scientists. Of the many dimensions of income inequality, we explore four, analysing a rich data set for China. Does actual or perceived inequality have a greater effect on happiness? We find that perceptions of inequality are the more important. How broad is the reference group with which people compare themselves? They report that it is narrow; and indeed narrowly defined inequality has the greater effect on happiness. Do perceptions of the degree of fairness of inequality matter? They do, as they ameliorate the adverse effect of inequality on happiness, especially for the poorest. Is it self-centred or community-based inequality which affects happiness? Both measures have significant effects, but in opposite directions. The research and policy implications are discussed.